Labour market praticipation and mortage related borrowing constraints - Renata Bottazzi (Institute for Fiscal Studies (IFS), 2004)
This paper analyses the relationship between female labour market participation and mortgage commitments in life-cycle set up. In particular it examines whether a mortgage qualification constraint has any effect on female labour market participation. This is done by conditioning on the mortgage decision in a labour market participation equation for married women. Endogeneity of the mortgage variable is tested using house price data. Panel data from the British Household Panel Study is used in order to control for unobserved heterogeneity in participation.
Keywords: J40; D91; 330; Mortgages; labour market participation; women; Erwerbstätigkeit; Weibliche Arbeitskräfte; Arbeitsangebot; Hypothek; Großbritannien